An economic case for a UK collective collection. Issue 1 (6th July 2015) - Ball, David
Abstract : Purpose: – This paper is a thought experiment that investigates the possibilities of moving from the typical "just-in-case" model of managing legacy collections of printed monographs to a centralised "just-in-time" model. Design/methodology/approach: – Reliable published statistical data have been used; the core of these are the annual library statistics for UK research libraries collected by SCONUL. From these and other sources, the costs of monograph storage across UK research libraries have been determined. Findings: – Establishing a centralised collective collection would bring a large return on investment. Research limitations/implications: – This is not an empirical study. Originality/value: – The value of this study is high.